Working for the Hierarchical System: The Role of Meritocratic Ideology in the Endorsement of Corruption. Issue 3 (3rd May 2016) - Tan, Xuyun; Liu, Li; Huang, Zhenwei; Zheng, Wenwen
Abstract : Corruption has a wide range of corrosive effects on societies, but it is widespread throughout the world. There is a question, however, as to whether corruption is endorsed as an outcome of a legitimate hierarchy and meritocracy. To address this issue, the present study examines the associations between meritocratic ideology and the indicators of corruption by performing two empirical studies with correlational and experimental designs. In Study 1, all variables were measured with scales, and the results demonstrated that meritocratic ideologies were negatively associated with corruption perception but positively associated with corrupt intention. In Study 2, meritocratic ideology was manipulated, and the results demonstrated that compared with the low meritocratic‐ideology condition, the participants primed by the high meritocratic‐ideology condition reported a lower corruption perception but higher corrupt intention. In both studies, the findings suggest that the meritocratic ideology that motivates people to maintain and bolster the current hierarchical structure and meritocracy leads to the endorsement of corruption. The present study explores the roles of meritocratic ideology in the perception and intention of corruption, extends the scope of the predictive power of system justification theory to corruption beyond mere injustice‐related aspects of disadvantage, and also provides suggestions for interpreting and fighting against corruption.